Філософські основи здоров’я орієнтованого змісту професійної підготовки студентів-управлінців - Завидівська, Ольга (My University, 2018)
Розглядаються загальні філософські основи здоров’яорієнтованого змісту професійної підготовки студентів-управлінців. Висвітлено основні напрямки навчання майбутніх менеджерів з урахуванням філософських ідей. Обґрунтовано філософські погляди і уявлення про природу людини та суспільства. Проаналізовано філософські аспекти здоров’яорієнтованого змісту навчання майбутніх менеджерів на основі постнекласичної методології. Визначено основні концептуальні положення змісту фахової підготовки студентів-управлінців на засадах здоров’язбережувального навчання. Йдеться про те, що професійна підготовка студентів-управлінців має сприяти формуванню у них орієнтованих на кожну людину, індивідуальних, більш високого рівня, здоров’яорієнтованих управлінських навичок. The general philosophical bases of the health-oriented essence of professional training of students-managers are considered. The main directions of future managers' study on the basis of philosophical ideas are considered. The philosophical views and ideas about the nature of human and society are substantiated. The philosophical aspects of the health-oriented essence of the training of future managers on the basis of postnonclassical methodology are analyzed. The main conceptual provisions of the essence of professional training of students-managers on the basis of health preserving study are determined. The point is about that the professional training of students-managers should contribute to the formation of their individual, oriented on every person, the higher-level health-oriented managerial skills. The characteristics of professional mastery of modern manager are revealed. The necessity of combining ontological and epistemological aspects in the system of professional training of students-managers is declared. Future managers in the conditions organization must increasingly recognize the neediness for introduction complex systems of health preserving measures for employees. It was stated that the pedagogical paradigm of the development of professional training of students-managers should organically include the concept of noospheric study as a new fundamental basis of their professional education in general. The noospheric pedagogical paradigm should determine the pre-eminent nature of the process of forming the readiness of students-managers to create a health-oriented environment of organization in the future.
Keywords: філософські основи; концептуальні засади; студенти-управлінці; професійна підготовка; здоров’я орієнтоване навчання